Mental, physical and socio-economic status of adults living in spain during the late stages of the state of emergency caused by COVID-19 - Sánchez-Rodríguez, Elisabet (2022)
Research has shown that the confinement measures implemented to curb the spread of COVID-19 can have negative effects on people’s lives at multiple levels. The objective of this cross-sectional study was to better understand the mental, physical, and socio-economic status of adults living in Spain during the late stages of the state of emergency caused by COVID-19. Five hundred and forty-four individuals responded to an online survey between 3 June and 30 July 2020. They were asked to report data about their mental and physical health, financial situation, and satisfaction with the information received about the pandemic. Means, percentages, t-test, ANOVAs, and logistic regressions were computed. A third of the participants reported symptoms of anxiety, depression, and stress, and worries about their health and the future. Participants also described mild levels of fatigue and pain during lockdown (66%), and a reduction in household income (39%). Respondents that were female, younger, single, and with lower levels of education reported experiencing a greater impact of the COVID-19 pandemic. The data showed that the negative effects of lockdown were present in the late stages of the state of emergency. The findings can be used to contribute to the development of programs to prevent or mitigate the negative impact of confinement measures.